The information activity of rail passenger information staff: a foundation for information system requirements - Martin Rose (Information Research: An International Electronic Journal)
Introduction. This paper examines the goal-directed information activity of passenger information staff, working in the dynamic environment of rail network control. The explicit aim is to define a meaningful set of information system requirements. The report shows how dynamic situations may lead us to question a number of established theories of information science. Method. Passenger information officers (PIOs) were observed on duty within the rail command and control headquarters. Observation sessions totally eight hours involved the manual recording of sequential information flows and the associated activity of PIOs. A semi-structured management interview was also conducted to provide further insight into the organizational context. Analysis. A viewpoint-oriented analysis technique was used to analyse sequential data captured during observation sessions. Event sequences that represent and explain the viewpoints were identified and elaborated into detailed scenario descriptions. Results. The analysis both supports and contests a number of established theories from information science. Additionally, a range of 'mandatory' and 'desirable' system requirements are derived from the scenario and viewpoint analyses. Conclusion. Dynamic situations have a significant impact on information behaviour which is not always predicted by current theories of information science.